Foundations and future application of internet–based interventions for PTSD in PR China. (27th August 2012) - Wang, Zhiyun; Tang, Suqin; Wang, Jianping; Maercker, Andreas
This study examines internet–based interventions as a solution to improve mental health services for traumatised individuals in People's Republic of China (PR China). By reviewing the literature, the authors first summarise primary barriers to Chinese people's mental health help–seeking. Next, based on a research model, the authors discuss how the internet has been used to overcome these barriers and then introduce the current state of internet–based interventions. Finally, the authors conclude the necessity and feasibility of internet–based intervention applications in PR China, give implications for mental health services and discuss some limitations.